2008
DOI: 10.1080/07315724.2008.10719682
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Metabolism and Antioxidant Status in Sucrose vs. Potato-Fed Rats

Abstract: Our present results suggest that consumption of complex carbohydrates (provided as cooked potatoes), in combination with different antioxidant micronutrients, may enhance the antioxidant defences and improve lipid metabolism, when compared with starch (complex carbohydrates) and to sucrose consumption (source of simple sugar). These effects limit oxidative stress and reduce the risk of developing the associated degenerative diseases, including cardiovascular disease, and could have potential in cardiovascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 49 publications
2
11
0
Order By: Relevance
“…The only exception was serum cholesterol, which was diminished to a lesser degree in MCD-starch mice than MCDsucrose mice. Serum cholesterol was lower in starch-fed control (MCS) mice than sucrose-fed control mice, consistent with previous reports documenting the hypocholesterolemic nature of complex dietary carbohydrate (28)(29)(30). Why this same effect was not observed in the MCD groups with different dietary carbohydrate is unknown.…”
Section: Resultssupporting
confidence: 78%
“…The only exception was serum cholesterol, which was diminished to a lesser degree in MCD-starch mice than MCDsucrose mice. Serum cholesterol was lower in starch-fed control (MCS) mice than sucrose-fed control mice, consistent with previous reports documenting the hypocholesterolemic nature of complex dietary carbohydrate (28)(29)(30). Why this same effect was not observed in the MCD groups with different dietary carbohydrate is unknown.…”
Section: Resultssupporting
confidence: 78%
“…Likewise, higher levels of liver and serum triglycerides were found in the HS group, as described in other studies [17,37,38] . Although fructose is considered a hypertriglyceridemic sugar and is thought to account for the hypertriglyceridemic effect of sucrose [39] , sucrose intake appears to be also associated with increased triglyceride levels in humans [40] .…”
Section: Discussionsupporting
confidence: 73%
“…The main dietary carbohydrates, starch or sucrose, may differentially affect lipid metabolism and the antioxidant status in rats, by potentially impacting on triglyceride clearance and because of the supply of antioxidant micronutrients provided by complex sugars in comparison to the refined ones [37] . It could probably be related to an increase in liver lipogenesis, converting sugar surplus into triglycerides.…”
Section: Discussionmentioning
confidence: 99%
“…Another study on the lipid-lowering effect of potato in rats showed that feeding rats a potato-enriched diet led to a decrease in cholesterol and triglyceride levels in plasma, decreased cholesterol level in the liver and improved antioxidant status (Robert et al, 2006, Robert et al, 2008. These results suggest that potato consumption may enhance antioxidant defense and improve the lipid metabolism.…”
Section: Carotenoids and Polyphenolsmentioning
confidence: 81%